KONSEP PAWONGAN SEBAGAI DASAR PEMENUHAN HAK DAN KEWAJIBAN DALAM AWIG-AWIG SEKAA TERUNA CANTHI GRAHA DI BANJAR TENGAH DESA ADAT SESETAN - Adi Widnyana I Made (VYAVAHARA DUTA, 2022)
Bali has several provisions of customary law that have existed and applied from the past as a wealth that becomes a guideline for the people of Bali in life. Customary law in Bali there are several types, one of which is awig-awig. The provisions of awig-awig are owned by almost all traditional indigenous organizations in Bali, one of which is the organization of sekaa teruna. The content of the awig-awig cargo cannot be separated from the value of balinese local wisdom that is respected, one of which is Tri Hita Karana, which includes, parhyangan, pawongan and palemahan. The purpose of this paper is to show that the concept of pawongan which is part of Tri Hita Karana can be applied in the awig-awig material and becomes an important part in explaining the relationship of rights and obligations of members. From the analysis conducted by the customary legal order in Bali there are in various forms such as awig, awig, perarem, eka eli kita, and others. The concept of Tri Hita Karana exists in the form of parhyangan, pawongan and palemahan relationships. In the preparation of Awig-Awig Sekaa Teruna Canthi Graha using the concept of pawongan as the basis for fulfilling the rights and obligations included in the provisions of self-driving pawongan and olih-olihan sekaa teruna.